2009
DOI: 10.1538/expanim.58.409
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Pancreatitis Model WBN/Kob Rat Strain Has a Unique Haplotype in the Pdwk1 Region on Chromosome 7

Abstract: Abstract:The WBN/Kob rat strain is a hereditary animal model of chronic pancreatitis and diabetes mellitus. The major WBN/Kob loci for pancreatitis (Pdwk1 and Pdwk2) are located on chromosomes 7 and X, respectively. In this study, polymorphisms were sought for candidate genes in the Pdwk1 and Pdwk2 regions. Nucleotide polymorphisms were found in 14 candidate genes examined in the Pdwk1 region. These polymorphisms were not associated with functional changes, and hence were unlikely to be a cause of pancreatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Mitochondrial swelling after ischemia and stasis of pancreatic juice were further reported to be responsible for early pancreatic changes [125,126]. Chromosomal mapping of WBN/Kob rats showed a unique haplotype block in the chromosomal region Pdwk1 (pancreatitis and diabetes mellitus in WBN/Kob locus 1) on chromosome 7 after identification of nucleotide polymorphisms of three candidate genes that were not found in other inbred rat strains [127]. These genes ( Rac2 , Grap2 and Xpnpep3 ) exert different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial swelling after ischemia and stasis of pancreatic juice were further reported to be responsible for early pancreatic changes [125,126]. Chromosomal mapping of WBN/Kob rats showed a unique haplotype block in the chromosomal region Pdwk1 (pancreatitis and diabetes mellitus in WBN/Kob locus 1) on chromosome 7 after identification of nucleotide polymorphisms of three candidate genes that were not found in other inbred rat strains [127]. These genes ( Rac2 , Grap2 and Xpnpep3 ) exert different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuji et al identified two highly significant QTLs for chronic pancreatitis and/or hyperinsulinemia on chromosomes 7 and X [29]. Mori et al reported that Pdwk1 (on chromosome 7) was a candidate gene for pancreatitis in the WBN/Kob rat [17].…”
mentioning
confidence: 99%
“…Diseases of exocrine pancreas such as chronic pancreatitis and AP adversely affect endocrine function and may lead to diabetes [47]. Pancreatitis and secondary diabetes are observed in WBN/KOb rats [48] and severity of pancreatitis and diabetes increases in WBN/Kob-Leprfa strain with homozygous fa/fa trait (genetic obesity), as compared to parental WBN/KOb rats. These homozygous (fa/fa) WBN/ Kob-Leprfa rats with obesity develop pancreatitis at the age of 7 -9 weeks compared to 3 months in WBN/Kob rats, and develop diabetes by the age of 3 -4 months as compared to 9 months in male WBN/Kob rats [49].…”
Section: Discussionmentioning
confidence: 99%